Кранты: [роман] / Михаил Серегин - Серегин Михаил Георгиевич (Блатари и уркаганы, 2009)
Экземпляры: ЧЗ (20201117) / Инвентарный номер: 48020 / Цена: 60.00 / Сис.шифр: 84(2=411.2)6-44 / Авт.знак: С 32 / ГРНТИ: 17.82 / ББК: 84(2=411.2)6-44